Computational Methods for Polymers - Soroush, Masoud; Soroush, Masoud (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents recent advances in computational methods for polymers. It covers multiscale modeling of polymers, polymerization reactions, and polymerization processes as well as control, monitoring, and estimation methods applied to polymerization processes. It presents theoretical insights gained from multiscale modeling validated with exprimental measurements. The book consolidates new computational tools and methods developed by academic researchers in this area and presents them systematically. The book is useful for graduate students, researchers, and process engineers and managers.
English
Keywords: History of engineering & technology; rapid tooling; additive manufacturing; failure modes; injection molding; modeling; olefin; gas phase; kinetics; hyperbranched; Monte Carlo simulation; radius of gyration; span length; continuous stirred-tank reactor; data-driven parameter estimation; retrospective cost model refinement algorithm; global sensitivity analysis; polyolefin synthesis; olefin copolymerization; reactivity ratios; electronic effects; salan catalysts; post-metallocene; DFT; insertion kinetics; olefin capture; PolyEThyleneAmidoAmine (PETAA) dendrimer; molecular topological indices; Eccentric connectivity index; copolymerization; design of experiments; reactivity ratio estimation; terpolymerization; PLP-SEC; n-butyl acrylate; degree of branching; nanostar dendrimer; irregularity measure; complexity of structure; NS1[p]; NS2[p]; NS3[p]; subspace identification; polymer processing; model predictive control; rotational molding; batch process modeling and control; method of moments; free-radical polymerization; methyl acrylate; thermal polymerization; high-temperature polymerization; molecular graph; irregularity indices; dendrimers; density functional theory; inhibitors; phenolic; stable nitroxide radicals; styrene